2005
DOI: 10.1111/j.1540-8183.2005.00042.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Non‐Q wave Myocardial Infarction Following Percutaneous Coronary Intervention in the Stent Era: Systematic Monitoring of the Three Markers of Myocardial Necrosis

Abstract: The elevation of at least one biochemical marker of myocardial necrosis is frequent following successful PCI with routine stent implantation. CK-MB mass is the most practical marker, having optimal kinetic and peaking with the first 12-18 hours post-PCI. Definitive data on the prognostic role and the applicability for the diagnosis of myocardial infarction of minor elevation of CK-MB mass or isolated increase of TnI are lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The primary endpoint in our meta-analysis was not specifically reported in four studies [20,22,30,31]. In one older study with a very small sample size of 23 patients, an unusually high cut-off value for troponin T was used, and therefore this study was excluded [32].…”
Section: Methodsmentioning
confidence: 95%
“…The primary endpoint in our meta-analysis was not specifically reported in four studies [20,22,30,31]. In one older study with a very small sample size of 23 patients, an unusually high cut-off value for troponin T was used, and therefore this study was excluded [32].…”
Section: Methodsmentioning
confidence: 95%
“…12 Abnormal postprocedural troponin elevations have been documented in at least 50% of patients undergoing PCI. 5,13 In a recent prospective multicenter cohort study that included 3494 consecutive patients undergoing PCI, abnormal postprocedural CK-MB and cTnI values were found in 16% and 44% of patients, respectively. 14 In our population of stable patients undergoing elective single-vessel PCI, the rates of abnormal CK-MB and cTnI elevation after intervention (10% and 46% of cases, respectively) were similar to those reported by others.…”
Section: Myocardial Damage After Uncomplicated Pcimentioning
confidence: 99%
“…14 In our population of stable patients undergoing elective single-vessel PCI, the rates of abnormal CK-MB and cTnI elevation after intervention (10% and 46% of cases, respectively) were similar to those reported by others. 13,14 A recent meta-analysis of 23 230 patients undergoing PCI in 7 large prospective trials showed that long-term mortality risk increases at any level above normal postprocedural CK-MB, 15 although in most studies postprocedural elevation of CK-MB, but not of cTnI, has been found to influence long-term mortality. 14,16 However, even mild cTnI elevation after PCI has been shown to be associated with discrete microinfarction findings on contrast-enhanced MRI studies.…”
Section: Myocardial Damage After Uncomplicated Pcimentioning
confidence: 99%
“…Previous studies have reported in 5.5-15% of patients had CK-MB elevation 3 times the upper limit of normal, 2.5-3% of patients had CK-MB elevation 5 times the upper limit of normal, and 35-50% of patients had cardiac troponins elevation above the upper limit of normal after PCI [28,33]. Chen and colleagues reported 37.9% of aspirin resistant patients had CK-MB elevation 1-3 times the upper limit of normal and 10.3% of aspirin resistant patients had CK-MB elevation 3-5 times the upper limit of normal.…”
Section: Discussionmentioning
confidence: 97%